2017
DOI: 10.25077/ar.4.1.27-37.2017
|View full text |Cite
|
Sign up to set email alerts
|

A Phonological Analysis on the English Consonants of Sundanese EFL Speakers

Abstract: This descriptive qualitative study focuses on the description of the English consonants systems spoken by speakers of Sundanese backgrounds. This implies that such speakers of particular regional backgrounds speak unique and ideosyncratic native languages. This study will provide a description on the consonants production of English as Foreign Language (EFL) speakers with Sundanese native language in an experimental phonetic method to the students of Islamic Education Department of State Institute for Islamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Phoneme change is a common process in a language change (Hruschka et al, 2015). Phoneme change could be caused by several factors, namely geographical, social and historical factors (Risdianto, 2017). Based on the result of the study, it is seen here that this study is successful in investigating the qualitative data as the existences of the interrelatedness of PAn to PSm-Te since some PSm-Te etymons were found showing phoneme correspondences between the two protoes.…”
Section: Discussionmentioning
confidence: 61%
“…Phoneme change is a common process in a language change (Hruschka et al, 2015). Phoneme change could be caused by several factors, namely geographical, social and historical factors (Risdianto, 2017). Based on the result of the study, it is seen here that this study is successful in investigating the qualitative data as the existences of the interrelatedness of PAn to PSm-Te since some PSm-Te etymons were found showing phoneme correspondences between the two protoes.…”
Section: Discussionmentioning
confidence: 61%
“…On the other hand, Al-Rubaat and Alshammari (2020) revealed that learners experienced errors in phonology related to mispronunciation of voiced or voiceless phonemes. In his study, Risdianto (2017) concluded that EFL Sudanese students' greatest errors in spoken English is on mispronouncing consonant minimal pairs such as /f/ and /v/, /s/ and /Ө/ and /ð/ and /z/. Safrida (2016) determined that the students still have a serious problem in terms of grammatical aspect, especially omission of noun inflections and irregular past tenses, and malformation of auxiliaries while the study of Mardijono (2003) revealed that there are more occurrences of syntactic errors compared to morphological errors.…”
Section: Linguistic Category Taxonomy Of Errorsmentioning
confidence: 95%
“…Several studies have investigated the phonological analysis of English sounds produced by non-native speakers. The research conducted by Risdianto (2017) aims to identify the English consonant system of EFL Sundanese speakers and investigate the most frequent errors on pronouncing English consonants. This study was conducted through a production experiment and applied the theories of consonants system proposed by Ramelan (2003).…”
Section: Introductionmentioning
confidence: 99%